PRODUCTION OF DOCOSAHEXAENOIC ACID (DHA) FROM Thraustochytrium sp. ATCC 26185 USING DIFFERENTS NITROGEN CONCENTRATIONS - FURLAN, VALCENIR JÚNIOR MENDES; PAULO, MARIA DO CASTELO; MAUS, VICTOR WEGNER; FERREIRA, JÚLIA; BATISTA, IRINEU; BANDARRA, NARCISA MARIA (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2017)
Polyunsaturated fatty acids (PUFAs) of the type ω3 and ω6 play important physiological functions in human organism, since they are components of cell membranes and brain cells; they decrease the levels of triglycerides and can prevent the incidence of coronary heart disease. Various parameters, including concentration of the nitrogen source in the cultivation of oleaginous microorganisms have been reported to be essential in the biosynthesis and accumulation of PUFAs. The objective of this work is to study the effect of different concentrations of total nitrogen (TN) in the production of PUFAs, especially DHA, from Thraustochytrium sp. ATCC 26185. The concentrations of TN evaluated were 2.4 and 0.8 g/L (batch) and 0.009 g/L (hourly) under fed-batch process. The content of cell biomass, glucose consumption, TN and production of PUFAs was determined. The major composition of the PUFAs in Thraustochytrium sp. ATCC 26185 cell biomass were DPA ω6 (21-25%) and DHA (69-73%), regardless of the type and time of culture. The maximum cell concentration obtained (30.2 g/L) was using 2.4 g/L TN in 168 h of culture. With this same concentration of TN it was possible to produce the highest concentration of DHA (1.16 g/L) in 120 h of culture, demonstrating that the growth of Thraustochytrium sp. ATCC 26185 and yield of PUFAs are dependent on the concentration TN source available for consumption of this oleaginous microorganism, as well as culture time